DIAGNOSTIC VALUE OF TUMOR MARKER CA-125 IN THE EARLY DIAGNOSIS OF OVARIAN CANCER - Светлана Ивановна Елгина; Ольга Сергеевна Золоторевская; Анастасия Игоревна Тимаева (The Publishing House Medicine and Enlightenment, 2020)
Objective - to determine the diagnostic significance of the cancer marker CA-125 in the early stages of ovarian malignancy, its sensitivity and specificity. Materials and methods. A retrospective analysis of the medical histories of 44 women operated in gynecological hospitals of the General network with neoplasms in the area of the uterus appendages for the period from 2016 to 2019 was carried out. Ovarian neoplasms in women were detected on an outpatient basis during gynecological examination in the Kemerovo city clinical hospital N 4 women's consultation, confirmed by ultrasound. All women were assessed for baseline CA-125 in the scope of a comprehensive preoperative examination. Blood was taken from a vein, in the morning, on an empty stomach, on the 2-3 day of the menstrual cycle, in postmenopausal women on any day. The recommended threshold level for CA-125 is less than 35 IU/ml. Statistical data analysis was performed using the Microsoft Office Excel 2010 application software package (license agreement 7401764000001067177) and Stat Soft Statistica 6.1 (license agreement BXXR006D092218FAN11). After receiving the results of the study, sensitivity, specificity, and predictive value were determined for CA 125. The results of the study were processed using Statistics Trial and Microsoft Excel. Results. At the outpatient stage, 33 (75 %) women had a normal CA score of 125, 11 (25 %) - higher than the norm. Excess of CA-125 twice or more was diagnosed in 7 (16 %) women. In connection with its increase, the patients were consulted by an oncologist. After surgical treatment in various volumes, the results of the histological study were presented with Brenner's tumor in 2 %, serous adenocarcinoma in 7 %, endometrioid cyst in 9 %, follicular cyst in 9 %, Mature teratoma in 11 %, tecoma in 11 %, fibroma in 16 %, and serous cystadenoma in 34 %. When comparing the results of CA-125 and morphological diagnosis, matches were found in 45 % of cases. Specificity was 75 %, sensitivity - 80 %. Conclusion. Thus, based on the data from our study, the determination of the tumor-associated CA-125 antigen is not a strictly specific screening marker for early diagnosis of ovarian cancer.